Understanding Coffee Shop Consumer Preferences in Bandung: a Conjoint Analysis Approach for Nama Coffee’s Expansion - Denissa Aulia Putri; Dina Dellyana (Eduvest - Journal of Universal Studies, 2025)
Nama Coffee’s expansion to Bandung requires understanding local customer preferences to ensure successful market entry and brand preference cultivation. This involves identifying key attributes influencing customer choices in Bandung’s competitive coffee shop market. This research aims to (1) identify Bandung consumer preferences for Nama Coffee’s design and concept, (2) determine the importance of coffee shop attributes in shaping these preferences, and (3) develop strategies for Nama Coffee in Bandung. This research employs a quantitative survey design, targeting Bandung coffee shop consumers. Data collection involves online and in-person questionnaires, focusing on design, facilities, menu, service, price, and promotions. Conjoint analysis will identify key preference factors and their relative importance. A TOWS matrix analyzes Nama Coffee’s internal and external environment to inform strategic recommendations. Conjoint analysis revealed "Design" as the most influential factor for Bandung coffee shop selection, followed by "Promotion" and "Price." Respondents favored minimalist designs, B1G1 promotions, and competitive pricing. Correlation analysis confirmed the model’s accuracy in predicting preferences. Bandung coffee shop preferences prioritize minimalist design, B1G1 promotions, and competitive pricing. Nama Coffee should leverage these insights in their Bandung expansion, by implement minimalist design, optimize B1G1 promotions, adopt competitive pricing, enhance service quality, maintain coffee quality, utilize social media, and develop strategic partnerships. The BMC should focus on aligning with Bandung preferences, enhancing operational efficiency, and reinforcing marketing strategies.